2009
DOI: 10.1590/s0004-27302009000800014
|View full text |Cite
|
Sign up to set email alerts
|

Short term testosterone replacement therapy improves libido and body composition

Abstract: Objective: To assess the efficacy and safety of testosterone replacement in males with late-onset hypogonadism compared to hypogonadal men without replacement, and controls, during six months. Methods: We assessed, through ADAM, AMS, IIEF-5 and SF-36 questionnaires, and through clinical and laboratorial examinations, 62 patients divided into three groups: 17 hypogonadal males (HR) used intramuscular testosterone every three weeks; 14 hypogonadal males (HV) and 31 non-hypogonadal males (CV) used oral vitamins d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Of the studies included in this meta-analysis, the earliest was performed in 1997 by Sih et al, 30 who studied hypogonadal men with a mean age of 68 years and reported that testosterone supplementation (200 mg testosterone cypionate biweekly for 12 months) improved strength, increased hemoglobin levels, and lowered leptin levels. Andrade et al 2 also treated hypogonadal men with IM testosterone for 6 months and reported an improvement in body composition. Chiang et al 23 and Park et al 4 both reported that testosterone replacement improved quality of life and sexual function in men with testosterone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Of the studies included in this meta-analysis, the earliest was performed in 1997 by Sih et al, 30 who studied hypogonadal men with a mean age of 68 years and reported that testosterone supplementation (200 mg testosterone cypionate biweekly for 12 months) improved strength, increased hemoglobin levels, and lowered leptin levels. Andrade et al 2 also treated hypogonadal men with IM testosterone for 6 months and reported an improvement in body composition. Chiang et al 23 and Park et al 4 both reported that testosterone replacement improved quality of life and sexual function in men with testosterone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Data on body composition were provided but the study was excluded since hypogonadism was artificially induced in healthy men by the use of GnRH agonist (136) Cross-over RCT of the effects of T patch (50 mg/day) and sildenafil for 8 weeks on sexual function in hypogonadal men with erectile dysfunction. The combined therapy with PDE5 and T or placebo can influence the outcomes of the study (137) Observational cohort study before and after study between two groups of participants receiving T (T cyprionate 200 mg/3 weeks) or not. There are not data about circulating T both in baseline and at the end of the study.…”
Section: Referencesmentioning
confidence: 99%
“…The basic science literature has confirmed the necessity of androgens to generate adequate intracavernosal pressures and smooth muscle function to obtain an erection [59]. The literature showing the impact of testosterone replacement therapy (TRT) on erectile function is quite heterogenous (Table 1) [6061626364656667686970717273747576777879808182838485868788899091]. A subset analysis of the Olmstead County Cohort published by Gades et al [92] showed that testosterone has a statistically significant positive correlation with erectile function, even when adjusted for age.…”
Section: Hypogonadismmentioning
confidence: 99%